Advancing respiratory–cardiovascular physiology with the working heart–brainstem preparation over 25 years - Paton, Julian F. R.; Machado, Benedito H.; Moraes, Davi J. A.; Zoccal, Daniel B. [UNESP]; Abdala, Ana P.; Smith, Jeffrey C.; Antunes, Vagner R.; Murphy, David; Dutschmann, Mathias; Dhingra, Rishi R.; McAllen, Robin; Pickering, Anthony E.; et al. (Wiley, 2022)
Twenty-five years ago, a new physiological preparation called the working heart–brainstem preparation (WHBP) was introduced with the claim it would provide a new platform allowing studies not possible before in cardiovascular, neuroendocrine, autonomic and respiratory research. Herein, we review some of the progress made with the WHBP, some advantages and disadvantages along with potential future applications, and provide photographs and technical drawings of all the customised equipment used for the preparation. Using mice or rats, the WHBP is an in situ experimental model that is perfused via an extracorporeal circuit benefitting from unprecedented surgical access, mechanical stability of the brain for whole cell recording and an uncompromised use of pharmacological agents akin to in vitro approaches. The preparation has revealed novel mechanistic insights into, for example, the generation of distinct respiratory rhythms, the neurogenesis of sympathetic activity, coupling between respiration and the heart and circulation, hypothalamic and spinal control mechanisms, and peripheral and central chemoreceptor mechanisms. Insights have been gleaned into diseases such as hypertension, heart failure and sleep apnoea. Findings from the in situ preparation have been ratified in conscious in vivo animals and when tested have translated to humans. We conclude by discussing potential future applications of the WHBP including two-photon imaging of peripheral and central nervous systems and adoption of pharmacogenetic tools that will improve our understanding of physiological mechanisms and reveal novel mechanisms that may guide new treatment strategies for cardiorespiratory diseases.
Keywords: cardiac ganglion; cardiac vagus; chemoreceptor; eupnoea; gasp; hypertension; hypoxia; Kölliker–Fuse; pre-Bötzinger complex; respiratory rhythm generation; sympathetic; sympathetic-respiratory coupling